MENEBAR SPIRITUALITAS, MENJAGA BUDAYA: PERAN ROHANIWAN ASING DALAM DINAMIKA KEHIDUPAN KEAGAMAAN DI BALI - Elma Haryani (Harmoni, 2016)
This paper examines the contribution and the role of foreign proselytizers to the life of Hindu people in Bali. Assumingly, Hindu people in Bali are increasingly in need of new spiritual patterns, as they no longer experience the old religious pattern. As a result of the dynamic of new spiritual life. there is a need for them the arrival of foreign proselytizers to contribute to the local Hindu adherents. However, these foreign proselytizers must subject to certain regulatory requirements for receiving entry permit to Indonesia. This article adopts a qualitative approach and observation through in-depth interview. In addition, I also collected relevant documents and conducted a Focused Group Discussion (FGD). It is hoped that this paper can examine comprehensively what was happening in the field research.